STRATEGY TO DEFEND MALAY CULTURE AT KELURAHAN SUNGAI MEMPURA, KECAMATAN MEMPURA, KABUPATEN SIAK - Maizon, Rinda Hilda; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Kelurahan Sungai Mempura, Kecamatan Mempura, Kabupaten Siak. The purpose of this study is to know analyze the inhibiting factors in an effort to maintain the Malay at Kelurahan Sungai Mempura, Kecamatan Mempura, Kabupaten Siak. The focus of this research is the efforts of the government and the community in maintaining Malay Culture at Kelurahan Sungai Mempura, Kecamatan Mempura, Kabupaten Siak. The technique of determining samples in a purposive sampling and set the number of samples as many as 9 people. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation.Research conducted, the authors found that in maintaining the Malay culture, the effort of society is to preserve the Malay cultural values, inculcate the cultural habits of Malay and pass on the knowledge of Malay culture. The community is very guarding the culture that still survives at Kelurahan Sungai Mempura, Kecamatan Mempura, Kabupaten Siak and also introduces to the younger generation although there are some people who do not care anymore with local culture, people always do the habits of Malay culture in everyday life. Government efforts in maintaining Malay culture is by doing development, supervision and development. Inhibiting factors in maintaining Malay culture are tolerance, influence of outer culture or modernization, budget, community character, and ideological education. Factors that are very obstacles in maintaining Malay culture that is the character of society and ideological education because of the very open nature of society and high education makes people quickly recognize the outer western culture, which makes it difficult to maintain the Malay culture.Keywords: Culture, Effort, Factor, Malay